2020
DOI: 10.2174/0929867327666200316142659
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Oxysterols and Related Diseases

Abstract: The present review aims at providing a complete and comprehensive summary of current literature relevant to oxysterols and related diseases. Oxidation of cholesterol leads to the formation of a large number of oxidation products, generally known as oxysterols. They are intermediates in the biosynthesis of bile acids, steroid hormones, and 1,25-dihydroxyvitamin D3. Although oxysterols are considered as metabolic intermediates, there is a growing body of evidence that many oxysterols are bioactive, and their abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 175 publications
1
48
0
1
Order By: Relevance
“…Preventing the 7KC cytotoxicity by means of nutrients present in the Mediterranean diet (polyphenols, fatty acids) could be a means to counteract several diseases associated with oxidative stress leading to increased levels of 7KC mainly formed by cholesterol auto-oxidation [6,44]. In the present study, we showed that 7KC-induced cytotoxicity on murine neuronal N2a cells is characterized by ROS overproduction, alteration of plasma membrane, and drop of transmembrane mitochondrial potential (∆Ψm) leading to cell death.…”
Section: Discussionmentioning
confidence: 55%
“…Preventing the 7KC cytotoxicity by means of nutrients present in the Mediterranean diet (polyphenols, fatty acids) could be a means to counteract several diseases associated with oxidative stress leading to increased levels of 7KC mainly formed by cholesterol auto-oxidation [6,44]. In the present study, we showed that 7KC-induced cytotoxicity on murine neuronal N2a cells is characterized by ROS overproduction, alteration of plasma membrane, and drop of transmembrane mitochondrial potential (∆Ψm) leading to cell death.…”
Section: Discussionmentioning
confidence: 55%
“…An increased prevalence of fungal and Pseudomonas aeruginosa colonization has also been observed in patients with severe forms of COVID-19, suggesting that this association may be the result of a failure in the regulation of immune defenses against pathogens other than SARS-CoV-2, in the case of co-infection [ 55 ]. From a clinical point of view, atherosclerosis, AMD, cataract, and Alzheimer's disease are age-related diseases [ 42 , 56 ]. At the beginning of the pandemic, COVID-19 could be considered as an emerging age-related disease.…”
Section: Pathologies Associated With 7-ketocholesterolmentioning
confidence: 99%
“…With increased lifespans in human populations, the number of age-related diseases (cardiovascular diseases, eye diseases (cataract), age-related macular degeneration (AMD or ARMD)), neurodegenerative diseases (Parkinson’s disease, dementias and Alzheimer’s disease (AD), certain cancers) increase [ 1 , 2 , 3 ]. As these diseases have an important societal and financial impact, it is imperative to find drugs to decrease their frequencies.…”
Section: Introductionmentioning
confidence: 99%